The Myth of Rain in Wedding Ceremonies Jambak Tribe Community in Nagari Canduang Koto Laweh - Alfarezi, Muhammad; Endrizal, Endrizal; Septriani, Septriani (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research discusses "The Myth of Rain in the Wedding Ceremony of the Jambak Tribe in Nagari Canduang Koto Laweh". The purpose of this research is to find out how the background of the formation of myths and describe the views of the community related to the myth of rain in the wedding ceremony of the Jambak tribe in Minangkabau. The theory used in this research is the theory of Levi-Strauss Structuralism. The method used is qualitative method, with data collection techniques of field observation, interviews and documentation. The results of this study show that the myth of rain in the marriage of the Jambak tribe in Minangkabau originated from stories passed from mouth to mouth. The arrogant nature of the Jambak tribe in ancient times who insulted an old man who came asking for a little food because he saw they were holding a wedding party. In the end, the insult given by the host to the grandfather received an oath which eventually became a myth in the midst of society. At this time the people of Nagari Canduang Koto Laweh still believe in the myth. However, for the people of Nagari Canduang Koto Laweh, this myth is only believed and becomes a knowledge and is not fully believed even though it did rain when the Jambak tribe had a wedding. The community believes that whatever happens on earth happens with the permission of Allah SWT despite the myth. As an oral tradition, the rain myth in the wedding ceremony of the Jambak tribe in Minangkabau certainly has a meaning contained in it such as symbolic meaning, family meaning and customary meaning.